Peningkatan Hasil Belajar Ekonomi melalui Penerapan Model Contextual Teaching And Learning Berbasis Metode Edutainment - Dita Dwi Pratiwi; Kristiani Kristiani; Sudarno Sudarno (Departement of Mathematics Education, 2023)
This study aims to improve students' cognitive learning outcomes in Economics subject through the Contextual Teaching and Learning learning model based on the Edutainment method in class XI IPS 3 students at SMA Negeri 1 Gombong. This research is a collaborative Classroom Action Research (CAR). This research was conducted in three cycles. Each cycle consists of 4 stages, namely planning, action, observation, and reflection. The subjects in this study were 34 students of class XI IPS 3 at SMAN 1 Gombong. Data collection techniques include test and non-test techniques in the form of observation, interviews, field notes, and documentation. The results of this study indicate that the Contextual Teaching and Learning learning model based on the Edutainment method can improve student learning outcomes, especially in the cognitive domain, with the percentage of complete learning outcomes in cycle I reaching 32.4%, in cycle II the percentage of complete learning outcomes increases to 52.9 %, as well as in cycle III increased to 82.4%.